Rememorar y explicar: la imaginación del tiempo en el discurso histórico. Una lectura spinoziana - Ferlini Cartín, Héctor (Revista de Filosofía de la Universidad de Costa Rica, 2020)
<p class="_2-Texto-general" style="margin: 0px; padding: 0px; border-width: 0px; font-size: medium; line-height: 1.2; color: #000000; font-family: 'Times New Roman', serif; font-style: normal; font-variant: normal; font-weight: 400; orphans: 2; break-after: auto; break-before: auto; text-align: justify; text-align-last: left; text-decoration: none; text-indent: 18px; text-transform: none; widows: 2; letter-spacing: normal; white-space: normal; word-spacing: 0px; -webkit-text-stroke-width: 0px;">This article arges that the historiographic production founded exclusively on memory lacks a strong conceptualization. In consequense, this text proposes a theoretical framework for memory based in Spinoza´s philosophy, and some afterthoughts about the scientificity of the historical discourse.